1-Hz Repetitive Transcranial Magnetic Stimulation over the Posterior Parietal Cortex Modulates Spatial Attention - Xu, Guang-qing; Lan, Yue; Zhang, Qun; Liu, Dong-xu; He, Xiao-fei; Lin, Tuo (Frontiers in Human Neuroscience, 2016)
Lesion and neuroimaging studies have suggested that regions in the posterior parietal cortex (PPC) are involved in visual spatial attention. The aim of this study was to investigate the potential effects in spatial attention resulting from a transient parietal impairment induced by 1 Hz repetitive transcranial magnetic stimulation (rTMS). We examined 50 healthy subjects using the Attention Network Test after first applying rTMS to right or left PPC. The right parietal rTMS, but not left PPC rTMS, caused a significant slowing in the mean reaction time (RT) to spatial cues during the ANT test. There were no significant effects of rTMS on mean RT under the no cue, center cue, and double cue conditions, or for each flanker type among the experimental groups. Moreover, after rTMS to the right PPC, test subjects displayed deficits in networks related to alerting and orienting, whereas they exhibited improvement following rTMS to the left PPC. These findings indicate that the right PPC serves an important function in spatial orienting and the alerting activities. We considered that the enhancement in spatial alerting and orienting function resulting from the commonly received idea of inter-hemispheric inhibition was the disinhibition of right PPC caused by the low frequency rTMS induced 'virtual lesions' of left PPC.